Implementasi Kebijakan Penanganan Tindak Kekerasan Terhadap Perempuan Di Kota Semarang Melalui Pusat Pelayanan Terpadu (PPT) SERUNI - Purnaningsiwi, Frismai Anggit; Sundarso, Sundarso; Rengga, Aloysius (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The policy implementation of the handling of violence againts women in semarang city through integrated services centre SERUNI, is one of policies by Semarang city government to facilitate, help, and accompany the victims of gender-based violence, to get justice demanded their rights by services provide through integrated services centre SERUNI, such as the handling of complaints, medical service, psychological-spiritual and rehabilitation service, legal assistance, repatriation and social integration. The purpose of this research is to find out and analyze the process of implementation, also the factors that support and hinder implementation. Based on Van Meter and Van Horn’s theory, factors that support and hinder such as the goals and basic/standard size policy, Resource policy, communication and Implementation Activities, the implementing Agency Characteristics, Social, political and economic conditions as well as the disposition of the Implementor. This research is qualitative research with a descriptive approach. The result of this research showed that the existence of SERUNI already well underway, its proven by the growing number of incoming cases and handle by SERUNI, but in its implementation still hampered by the lack of member’s commitment, the lack of resources availability, such as human, finance and facilities work. Based on the existence obstacles on the policy implementation of the handling of violence againts women in semarang city through integrated services centre SERUNI, the author provides recommendations to strengthening the role of SERUNI when counseling the victims, allocate the budget for the member institutions and fix the disbursement system, add facilities and infrastructure as well as providing adequate secretariat, more embracing the victim to open up, support the existence of specialized medical services for victims, handling the violence by involving two sides, both the victims and the doers, contact the victims continuity, improve the standart operating procedure, improve the coordination between the implementing agents, immediatelly legalize the federal regulations on the protection of women an children in Semarang, tried to input of another funds besides from APBD.